From Kitab Malay to Literary Indonesian: A Case Study in Semantic Change - Riddell, Peter G. (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2012)
This paper discusses semantic movement as evidenced in Malay/Indonesian Islamic texts. The primary text in focus provides an example of â€˜Abd al-Raâ€™Å«f al-SingkÄ«lÄ«â€™s Malay commentary on the Quran, TarjumÄn al-MustafÄ«d, produced around 1675. The study of the lexical data from this text is informed by comparative reference to three modern Indonesian texts of SÅ«rah YÅ«suf: Mahmoed Joenoesâ€™ rendering (1954), the official Indonesian government rendering drawn from Al-Quraan dan Terjemahnya (1974), and H.B. Jassinâ€™s rendering (1978). The goal of this paper will be to answer two questions. First, the semantic range of certain lexical items used in the â€˜Abd al-Raâ€™Å«f Quran commentary compare with the norms of late 20th century literary Indonesian. Second, the semantic change of differences identified in this comparative process.DOI:Â 10.15408/sdi.v19i2.362